The Impact of Integrating Internet of Things (IoT) Technology in Learning on Class Management Efficiency - Iwan Adhicandra; Fata Nidaul Khasanah; Mas’ud Muhammadiah; Sabri Sabri; Chandra Halim Maharaja (Journal of Computer Science Advancements, 2024)
Internet of Things (IoT) technology is something that is equipped with sensors and software so that it can send data over a network without human interaction. As a result, the Internet of Things can improve connectivity by connecting many devices via the internet, facilitating human interaction with machines. This research was conducted with the aim of increasing efficiency, reliability and innovation in the teaching and learning process. By using IoT, this research focuses on developing interactive and personalized learning media to increase students' understanding of technology. In addition, this research aims to improve teachers' abilities in using information technology to help students learn to use it. In conducting this research, researchers used quantitative methods in carrying out the research. The data obtained by the researcher was obtained through distributing questionnaires presented by the researcher via a goggle from application. The distribution of this questionnaire is carried out by researchers online, and then the results of the distribution of this questionnaire will be processed using an SPSS application. From this research, researchers can conclude that the integration of Internet of Things (IoT) technology can increase classroom management efficiency. With the help of the Internet of Things (IoT), teachers can monitor and manage classes more efficiently and intelligently by collecting data such as student activity, room temperature, and other information. Thus, IoT allows teachers to make smarter and strategic decisions about classroom management. Based on the results of this research, the impact of integrating IoT technology can provide benefits for teachers and students. Developing digital skills is one of the benefits of integrating IoT technology. By learning how to use Internet of Things technology in learning, teachers can improve their digital skills and increase their ability to use technology to improve the efficiency and quality of education.